(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper explores the evolving landscape of youth culture in India, characterized by a rich interplay of tradition and modernity. As the nation’s youth—over 600 million strong—grapple with rapid globalization, technological advancements, and socio-political changes, their cultural expressions reflect diverse identities and aspirations. The study delves into key trends shaping contemporary Indian youth culture, including the rise of digital media, which has transformed communication, self-expression, and activism. Social media platforms have become vital spaces for discourse on pressing issues such as gender equality, mental health awareness, and environmental sustainability, enabling young people to challenge societal norms and advocate for social justice. The paper also examines the burgeoning start-up culture, where entrepreneurial ambitions are redefined, empowering youth to explore non-traditional career paths. This entrepreneurial spirit is complemented by the fusion of global and local influences, resulting in cultural hybridity that permeates fashion, music, and cuisine. Additionally, the emphasis on fitness and wellness trends highlights a growing awareness of health and holistic living among young Indians. Through qualitative analysis and case studies, this research aims to highlight the multifaceted nature of youth culture in India and its implications for broader societal transformation. By understanding these trends and influences, we can better appreciate the unique position of Indian youth as active participants in shaping their futures and redefining cultural narratives. Ultimately, this exploration underscores the significance of youth culture as a dynamic force, driving social change and fostering a more inclusive and progressive society in India.